Epidemiological characteristics of Candida species colonizing oral and rectal sites of Jordanian infants - Issa, Shireen Y; Badran, Eman F; Akl, Kamal F; Shehabi, Asem A (BMC pediatrics, 2011)
Background There is evidence that Candida colonization contributes to increasing invasion of candidiasis in hospitalized neonates. Few studies investigated the epidemiology and risk factors of Candida colonization among hospitalized and non-hospitalized infants. This prospective study investigated the major epidemiological characteristics of Candida species colonizing oral and rectal sites of Jordanian infants. Methods Infants aged one year or less who were examined at the pediatrics outpatient clinic or hospitalized at the Jordan University Hospital, Amman, Jordan, were included in this study. Culture swabs were collected from oral and rectal sites and inoculated on Sabouraud dextrose agar. All Candida isolates were confirmed by the Remel RapID yeast plus system, and further investigated for specific virulence factors and antifungal susceptibility MIC using E-test. Genotyping of C. albicans isolates was determined using random amplified polymorphic DNA (RAPD) analysis method. Results A total of 61/492 (12.4%) infants were colonized with Candida species by either their oral/rectal sites or both. Rectal colonization was significantly more detected than oral colonization (64.6% verses 35.4%), particularly among hospitalized infants aged more than one month. The pattern and rates of colonization were as follows: C. albicans was the commonest species isolated from both sites and accounted for 67.1% of all isolates, followed by C.kefyr (11.4%), each C. tropicalis and C. glabrata (8.9%) and C. parapsilosis (3.8%). A various rates of Candida isolates proved to secrete putative virulence factors in vitro ; asparatyl proteinase, phospholipase and hemolysin. C. albicans were associated significantly (P < 0.05) with these enzymes than other Candida species. All Candida isolates were susceptible to amphotericin B and caspofungin, whereas 97% of Candida species isolates were susceptible to fluconazole using E-test. The genetic similarity of 53 C. albicans isolates as demonstrated by dendrogram revealed the presence of 29 genotypes, and of these one genotype accounted for 22% of the isolates. Conclusion This study presents important epidemiological features of Candida colonization of Jordanian infants.